Role of enkephalin derivative in promoting wound healing and scar remodeling via increased epidermal growth factor in a mouse model - Sun Eung Kim; Yu Jin Kim; Young Woo Cheon (Archives of Aesthetic Plastic Surgery, 2023)
Background Enkephalin, an endogenous neuropeptide, binds to the delta (δ) opioid receptor and exerts an antinociceptive effect. Recent studies have suggested that neuropeptides might effectuate cutaneous wound healing. Therefore, we investigated the effects of an enkephalin derivative on wound healing and scar formation in vivo. Methods Enkephalin derivatives (leucine-enkephalin) were synthesized using the alanine scan method, and the most promising derivative (E10) was selected for further testing. In 15 C57BL/6N mice, two full-thickness skin defects (10 mm in diameter) were made on both sides of the back (left side, enkephalin group; right side, control group). The enkephalin group was administered 100 μL of E10 (AGGFL, 200 μg/mL), and the control group received phosphate-buffered saline. The wound size was digitally analyzed on days 2, 4, 7, and 10. After 21 days, the scar tissues were histologically evaluated for the scar depression index (SDI), and the epidermal growth factor (EGF) concentration was assessed using an enzyme-linked immunosorbent assay. Results The skin defect percentages were 98.4%±17.9% (day 2), 83.2%±24.0% (day 4), 39.7%±17.4% (day 7), and 16.2%±10.0% (day 10) in the control group and 86.1%±15.0% (day 2), 61.4%±11.6% (day 4), 26.6%±8.8% (day 7), and 16.4%±8.8% (day 10) in the enkephalin group. The SDI values were significantly lower in the enkephalin group (0.06±0.19) than in the control group (0.22±0.13, P<0.001). The EGF level was significantly higher in the enkephalin group (102.2±22.6 pg/mL) than in the control group (42.1±20.5 pg/mL, P<0.001). Conclusions An enkephalin derivative promoted wound healing and reduced depressed scar formation in a mouse model.